The fall of Waterstone - Saintcrow, Lilith (Saintcrow, Lilith. Black Land's bane, 2024)
"Solveig and her shieldmaiden have finally made it to Waterstone, a fabled city hidden in a world of frost by ancient magic. Shrouded from the Enemy's gaze, they are safe to rest and regroup-or so they think. Sol suspects their hosts are not as benevolent as they seem. Whispers race through the halls, hinting at self-serving agendas and secret plots. So, as Sol attempts to harness her awakened magic, she must fight for her voice to be heard or risk being used like a pawn in the greater game. But the Enemy always watching and nowhere is truly safe. Before the darkness finds a way in, Sol must decide if she will take up the mantle of power to save not just the home she's left behind, but the future of the world"--